PENGARUH CAREER EXPLORATION TERHADAP CAREER INDECISION YANG DIMEDIASI CAREER ANXIETY MAHASISWA DIPLOMA III FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS SYIAH KUALA - Suci Novia Pratiwi; Wirdah Irawati (Departemen Manajemen, Universitas Syiah Kuala, 2020)
This study aims to measure the effect of career exploration on career indecision and career anxiety as a mediation at college students of Diploma III in Economic and Business Faculty of Syiah Kuala University. The sample used in this study is college students of Diploma III in Economic and Business Faculty of Syiah Kuala University is totalling 203 respondents. Data collection equipment used in this study was a questionnaire. The sampling technique used is simple random sampling. Hierarchical Linear Modelling (HLM) was used as a method of analysis to determine the effect of all the variables involved. Based on the results of the HLM analysis indicated that career exploration was related to career indecision, career exploration significantly influence career anxiety, career anxiety was related to career indecision, career anxiety partially mediated the relationship between career exploration and career indecision.